2022
DOI: 10.1111/ijpo.12921
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal obesity and offspring gut microbiome in the first year of life

Abstract: Background: Maternal obesity is an important determinant of offspring obesity risk, which may be mediated via changes in the infant microbiome.Objectives: We examined infant faecal microbiome, short-chain fatty acids (SCFA), and maternal human milk oligosaccharides (HMO) in mothers with overweight/obese body mass index (BMI) (OW) compared with normal weight (NW) (Clinicaltrials.gov NCT01131117).Methods: Infant stool samples at 1, 6, and 12 months were analysed by 16S rRNA sequencing. Maternal (BODPOD) and infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Preliminary research on pregnant women with depression and anxiety has identified a strong link between modified bacterial abundance in the gut microbiota and inflammatory responses [ 133 ]. An equal association was observed with gestational diabetes mellitus [ 134 ], preeclampsia [ 135 ], maternal obesity [ 136 ], and fetal physical and mental developmental problems [ 137 ]. Therefore, the gut microbiota and the GBA play a crucial role during the prenatal period, when the maternal and fetal microbiota are sensitive, and any changes in the microbiota could affect fetal brain development.…”
Section: The Role Of the Gba In The Intergenerational Effects Of Brai...mentioning
confidence: 99%
“…Preliminary research on pregnant women with depression and anxiety has identified a strong link between modified bacterial abundance in the gut microbiota and inflammatory responses [ 133 ]. An equal association was observed with gestational diabetes mellitus [ 134 ], preeclampsia [ 135 ], maternal obesity [ 136 ], and fetal physical and mental developmental problems [ 137 ]. Therefore, the gut microbiota and the GBA play a crucial role during the prenatal period, when the maternal and fetal microbiota are sensitive, and any changes in the microbiota could affect fetal brain development.…”
Section: The Role Of the Gba In The Intergenerational Effects Of Brai...mentioning
confidence: 99%
“…Considering that the first microbial exposure of offspring is the maternal microbiota during pregnancy, it can be speculated that the gut microbiome and the subsequent metabolic and immunological programming are influenced by maternal nutritional status. In a cohort study performed on 170 pregnant women, infants born to overweight or obese mothers had a lower abundance of short chain fatty acid producing bacteria and lower fecal butyric acid levels at 1 month of age, which may contribute to predicting the risk of elevated adiposity later in life (Gilley et al, 2022). Germ-free mice colonized with stool microbes from 2-week-old human infants born to mothers with obesity had increased intestinal permeability, impaired macrophage activity and increased periportal inflammation compared with those colonized with stool microbes from infants born to mothers with normal weight.…”
Section: Altered Gut Microbiomementioning
confidence: 99%
“…Studies in humans estimate that the odds of developing childhood obesity for infants born to mothers with obesity are between 1.5 and 4 times higher when compared to infants born to mothers of normal weight ( 2 , 14 , 57 ). Research has shown that offspring born to women with obesity had lower levels of fecal butyrate as well as reduced abundance of SCFA-producing bacteria ( 58 ). Surprisingly, and in an opposite direction of what we would have expected, researchers also found that the microbiome of infants born to mothers with obesity had greater alpha-diversity at 12 months when compared to infants born to mothers of normal weight, and this alpha-diversity moderately predicted greater adiposity at 12 months of age ( 58 ).…”
Section: Maternal Obesity and The Infant Gut Microbiomementioning
confidence: 99%
“…Research has shown that offspring born to women with obesity had lower levels of fecal butyrate as well as reduced abundance of SCFA-producing bacteria ( 58 ). Surprisingly, and in an opposite direction of what we would have expected, researchers also found that the microbiome of infants born to mothers with obesity had greater alpha-diversity at 12 months when compared to infants born to mothers of normal weight, and this alpha-diversity moderately predicted greater adiposity at 12 months of age ( 58 ). Thus, it seems that the maternal obesity-associated development of the infant gut microbiome may contribute to the intergenerational transmission of the obesity phenotype ( Table 1 ).…”
Section: Maternal Obesity and The Infant Gut Microbiomementioning
confidence: 99%